ROLE OF BUSINESS GAME IN THE FORMATION OF CLINICAL THINKING AND COMMUNICATION SKILLS OF FUTURE DENTISTS - I.V. Gorb-Gavrilchenko (Український стоматологічний альманах, 2018)
The challenge of improving the quality of medical education of future doctors is facing faculty departments of higher medical schools. Preparation of the future doctor suggests not only an increase in the student's cumulative knowledge and information, but also the formation of professional thinking of clinical, psychological communication skills. These skills acquire special value in the study of one of the most important branches of therapeutic dentistry "periodontal disease".